2008
DOI: 10.1073/pnas.0708647105
|View full text |Cite
|
Sign up to set email alerts
|

PPARδ-mediated antiinflammatory mechanisms inhibit angiotensin II-accelerated atherosclerosis

Abstract: Activation of the nuclear hormone receptor peroxisome proliferatoractivated receptor ␦ (PPAR␦) has been shown to improve insulin resistance, adiposity, and plasma HDL levels. However, its antiatherogenic role remains controversial. Here we report atheroprotective effects of PPAR␦ activation in a model of angiotensin II (AngII)-accelerated atherosclerosis, characterized by increased vascular inflammation related to repression of an antiinflammatory corepressor, B cell lymphoma-6 (Bcl-6), and the regulators of G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
181
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(195 citation statements)
references
References 39 publications
13
181
0
1
Order By: Relevance
“…Other studies using PPARδ ligand have shown a reduction of inflammatory gene expression but not a decrease in atherosclerosis in LDLR −/− mice challenge with hypercholesterolemic diet [22]. Recently, Takata et al reported a reduction in atherosclerosis by PPARδ ligand in an angiotensin II accelerated LDLR −/− model [24].…”
Section: Ppars and Inflammationmentioning
confidence: 95%
“…Other studies using PPARδ ligand have shown a reduction of inflammatory gene expression but not a decrease in atherosclerosis in LDLR −/− mice challenge with hypercholesterolemic diet [22]. Recently, Takata et al reported a reduction in atherosclerosis by PPARδ ligand in an angiotensin II accelerated LDLR −/− model [24].…”
Section: Ppars and Inflammationmentioning
confidence: 95%
“…anti-inflammatory role of PPARδ in CS-related airway inflammation. It has been found that treatment with a synthetic PPARδ agonist inhibited activation of p38 MAP kinases in inflammatory circumstance, 19,28,32 which suggested a tight link between PPARδ and p38 MAPK. The MAPK family includes three members: p38, ERK and c-Jun N-terminal kinase (JNK).…”
Section: Discussionmentioning
confidence: 99%
“…WNT/β-Catenin Signaling Pathway Regulated CS-Stimulated Airway Inflammation by a PPARδ/p38 MAPK-Dependent Manner PPARδ, which has been reported to be involved in inflammation, 21,28 was a downstream target gene of WNT/ β-catenin signaling. 16 Our PCR results in Figure 3 showed that the mRNA levels of PPARδ were decreased by CSE stimulation.…”
Section: Cse-induced Inflammatory Cytokine Release Dependent On Wnt/βmentioning
confidence: 99%
“…PPARβ/δ -/-naïve CD4 + T cells are more prone to Th17 differentiation and hyper-responsive to TCR stimulation, as evidenced by the increased proliferation observed in these cells. Interestingly, PPARβ/δ has been hypothesized to bind the transcription factor B cell lymphoma 6 A B C (BCL6) and repress inflammation-related gene expression Takata et al, 2008;Varga et al, 2011).…”
Section: Ppars In T Cells and Autoimmunitymentioning
confidence: 99%